Pengaruh Budaya Organisasi Dan Pengembangan Sumber Daya Manusia Terhadap Kinerja Pegawai Pada Lembaga Penyiaran Publik TVRI: The Influence of Organizational Culture and Human Resource Development on Employee Performance at TVRI Public Broadcasting Institution - Syella Imania; Tri Lestari (CV Warnak Johanna Nusantara, 2025)
This research aims to determine the effect of Organizational Culture (X1) and Human Resource Development (X2) on Employee Performance (Y) at the Public Broadcasting Institution of the Republic of Indonesia in Central Jakarta, specifically in the Human Resources department. The method used is a quantitative approach with a saturated sampling technique, involving 40 respondents. Data collection was conducted through the distribution of questionnaires, and data analysis was performed using multiple linear regression with the aid of IBM SPSS Statistics 29 software. The results of the study indicate that organizational culture has a positive but not significant effect on employee performance, as shown by a coefficient value of 0.223 and a significance value of 0.058 > 0.05. Conversely, human resource development has a positive and significant effect on employee performance with a coefficient value of 0.807 and a significance of 0.001 (< 0.05). Simultaneously, organizational culture and human resource development have a positive and significant effect on employee performance, indicated by an F-value of 14.603 and a significance of 0.001 < 0.05. The conclusion of this study is that human resource development plays an important role in improving employee performance, although organizational culture has not shown a significant individual effect.